# Deriving the form of the second Frobenius solution when roots differ by an integer.

While using the Frobenius method to solve a second order ODE of the form

$$y^{\prime \prime} + p(x)y^\prime + q(x)y = 0$$

if the roots of the indicial equation $$(r(r-1)+p_0r+q_0=0)$$ $$r_1, r_2 (r_1>r_2)$$ differ by an integer then we first obtain $$y_1=\displaystyle \sum_{n=0}^{\infty} a_nx^{n+r_1}$$as a solution and then use reduction of order to find $$y_2$$. The formula for reduction for order is

$$y_2 = Cy_1\int\dfrac{e^{-\int p(x)dx}}{y_1^2(x)} dx$$

as derived here. Now, apparently you can derive the form of $$y_2$$ rigorously by substituting $$y_1=\displaystyle \sum_{n=0}^{\infty} a_nx^{n+r_1}$$ in the above eqaution. However, I cant find this derivation anywhere. If anyone knows how to derive

$$y_2 = Cy_1\ln x + x^{r_2}\sum_{n=0}^{\infty}b_nx^n$$

using this method or if there is ANY source/textbook that does this, please let me know.

• When $r_1-r_2$ is a positive integer, the power series method may (e.g. Bessel's DE of order $\frac12$: $x^2y''+xy'+(x^2-\frac14)y$) or may not (e.g. Bessel's order $1$) produce a second solution. You don't necessarily get the $y_1\log x$. Sep 27 at 15:16
• Yeah but when you do, how do we arrive at the form of $y_2$? Sep 27 at 17:47
• See math.stackexchange.com/questions/3907666/… for an exploration of this topic. The notation does not translate one-to-one, and there is something skewed in the first formula for the reduction-of-order here. Sep 28 at 8:10

First, the formula of reduction of order is $$y_2=\color\red{y_1}\int\frac{e^{-\int p(x)dx}}{y_1^2(x)}dx$$.
Also note that we can ignore $$C$$ since the solution $$c_1y_1+c_2y_2$$ already contains general constants.
To derive the given formula, let's start with evaluating $$\frac{1}{y_1^2(x)}=\frac{1}{x^{2r_1}(c_0+c_1x+c_2x^2+\cdots)}$$.
Let $$X=\frac{1}{c_0+c_1x+c_2x^2+\cdots}$$, and observe that $$X\cdot(c_0+c_1x+c_2x^2+\cdots)=1$$.
By comparing the coefficient of each term, we can know that $$X=\frac{1}{c_0}-\frac{c_1}{c_0^2}x+\frac{c_2c_0-c_1^2}{c_0^3}x^2+\cdots$$.
So we can say that $$\frac{1}{y_1^2(x)}=x^{-2r_1}(C_0+C_1x+C_2x^2+\cdots)$$ for $$C_0=\frac{1}{c_0},C_1=-\frac{c_1}{c_0^2},C_2-\frac{c_2c_0-c_1^2}{c_0^3},\cdots$$.
Now, observe that $$p(x)=\frac{a_0}{x}+a_1+a_2x+\cdots$$ so that $$e^{-\int p(x)dx}=e^{-a_0\ln(x)-a_1x-\frac{a_1}{2}x^2\cdots}$$
$$=x^{-a_0}e^{-a_1x-\frac{a_1}{2}x^2\cdots}=x^{-a_0}(1+R(x)+\frac{1}{2}\{R(x)\}^2+\cdots)=x^{-a_0}(1+d_1x+d_2x^2+\cdots)$$
where $$R(x)=-a_1x-\frac{a_1}{2}x^2\cdots$$, by using taylor series of $$e^x$$.
Thus we can write $$\frac{e^{-\int p(x)dx}}{y_1^2(x)}=x^{-2r_1-a_0}(D_0+D_1x+D_2x^2+\cdots)$$
$$=D_0x^{-2r_1-a_0}+D_1x^{-2r_1-a_0+1}+\cdots+D_{2r_1+a_0-1}\frac{1}{x}+\cdots$$.
Then $$\int\frac{e^{-\int p(x)dx}}{y_1^2(x)}dx=D_{2r_1+a_0-1}\ln (x)+\left[\frac{D_0}{-2r_1-a_0+1}x^{-2r_1-a_0+1}+\frac{D_1}{-2r_1-a_0+2}x^{-2r_1-a_0+2}+\cdots\right]$$.
Therefore $$y_2=y_1(x)\ln (x)+x^{r_1}(E_0x^{-2r_1-a_0+1}+E_1x^{-2r_1-a_0+2}+\cdots)$$.
Note that we divided RHS by $$D_{2r_1+a_0-1}$$.
Now, the proof ends by showing $$-r_1-a_0+1\geq r_2$$ and they differ by integer so that $$(E_0x^{-r_1-a_0+1}+E_1x^{-r_1-a_0+2}+\cdots)$$ can be written as $$x^{r_2}\sum_{n=0}^\infty b_nx^n$$.
Since $$r_1$$ and $$r_2$$ are the roots of the indicial equation $$r^2-(1-a_0)r+b_0$$, $$r_1+r_2=1-a_0$$.
Then $$-r_1-a_0+1=r_2$$, so they differ by an integer $$0$$, and the proof ends.
Moreover, we can know that $$b_0 \neq 0$$. (Your book may also mention this condition.)

• I'm sure Im missing something really obvious but how did you compare the coefficients of each term in $X$? Sep 28 at 15:04
• @AadhaarMurty First, multiply $\frac{1}{c_0}$ to $c_0+c_1x+c_2^2+\cdots$. Then we have $1+\frac{c_1}{c_0}x+\frac{c_2}{c_0}x^2+\cdots$. To eliminate $\frac{c_1}{c_0}x$, add $-\frac{c_1}{c_0^2}x(c_0+c_1x+c_2x^2+\cdots)$. Now the remaining is $-\frac{c_2c_0-c_1^2}{c_0^2}x^2+\cdots$. So add $\frac{c_2c_0-c_1^2}{c_0^3}x^2(c_0+c_1x+c_2x^2+\cdots)$. By repeating this steps, we can eliminate all terms except $1$. And by merging the terms we have added, $\left(\frac{1}{c_0}-\frac{c_1}{c_0^2}x+\frac{c_2c_0-c_1^2}{c_0^3}x^2+\cdots\right)(c_0+c_1x+c_2x^2+\cdots)=1$. Sep 29 at 11:21
• This concept is very similar to the division of polynomials, but different from the point that it starts dividing from the lowest order, constant. Sep 29 at 11:24
• If you already are normalizing arbitrary constants, you could also set $a_0=1$ so that also $c_0=1$, reducing complexity from the formulas. /// You should avoid double use of variable names in close context, here $a_k$ for the coefficients in $y_1$ and then in $p$. /// One should not discount the possibility that $D_{2r_1+a_0-1}=0$, removing the logarithmic term /// (Use display math environments - align, multline - for long formulas, it is better readable.) Sep 30 at 15:38
• @okw1124 thanks now it's clear. I get the rest of the solution. Last question though : could you just elaborate on how $p(x)\cdot x = a_0 + a_1x + a_2x^2...$ Oct 1 at 10:17